Penyuluhan Pemanfaatan Media Komunikasi dalam Membentuk Keluarga Sadar Literasi Digital - marlina marlina; Rizka Ar Rahmah (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
Internet-based communication media have become ubiquitous nowadays. Parents who care for their children’s physical and intellectual development and growth must always prioritize the process instead of the result. Pre-school children are constantly curious about new things. When they are faced with a situation that requires them to be familiar with internet-based media, they will enthusiastically tinker with any media that highly excite them. This interest will affect them negatively when the need turns into an addiction leading to chronic dependence on the media. Internet-based communication media are not something to be terrified at, but one must have a grasp of adept at them so they can be operated as a tool both for parental activities and for the pursuit of children development and growth. Family as the smallest organization but with a profound effect is expected to be able to serve as an early fortress of all outside information because a family that supports their children’s development and growth, especially their intellectual maturity, will turn a challenge into an opportunity. The formation of a digitally-aware family is essential in today's digital era. Being technologically literate allows one to cope with all incoming information. Awareness of digital literacy in the family is a prerequisite, especially for mothers since they are their family’s main madrasa as well as the primary overseer in their children’s development and growth.